Working Environment and Administrative Management in the Regional Directorate of Education of Lima (DRELP) - Roncal Aldaz, Dora Estelita (2020)
The research work aimed to identify if the work climate is related to administrative management in the Regional Directorate of Education of the Provinces of Lima (DRELP), Huara, Lima, 2016. A quantitative approach work was carried out, correlational type, Non-experimental correlational cross-sectional design. The study population consisted of 2,520 people, of whom 450 were managers. As for the sample, this can be selected based on a simple-random formula, between directors and teachers from the Lima Province Regional Directorate of Education, obtaining an optimal sample of 334 people; In addition, observation and survey will be used as data collection techniques, and the instrument used will be a Likert-style questionnaire made up of 18 items, according to the variables of the organizational climate, division into structural aspects and human resources, and the variable of administrative management, which was addressed to directors and teachers of the Regional Directorate of Education of Lima and Provinces and of the Local Educational Management Units. With a confidence level of 95%, it was concluded that there is a high positive level between the work climate and administrative management, since a Spearman’s Rho correlation coefficient of 0.848 was evidenced. From the variables an asymptotic significance value of 3.4% is obtained for a significance level of 5%, so the hypothesis is rejected and the working hypothesis is accepted.